Knowledge Discovery Melalui Pemodelan Topik pada Ulasan Pengguna Aplikasi GoPartner Menggunakan BERTopic, LDA, dan NMF - Pratiwi, Metti Detricia; Tania, Ken Ditha (Politeknik Negeri Batam, 2025)
Transportation and food delivery services are one of the driving sectors of the digital economy in Indonesia. The e-Conomy SEA 2023 report shows that the transportation and food delivery services sector experienced a decrease in GMV in 2023 by 8% from the previous year. The decline in GMV indicates a decrease in transaction value in the transportation and food delivery service sector. GoPartner is an application developed by GoTo to assist driver partners in carrying out various services in the gojek application which is one of the applications engaged in the transportation sector and food delivery services. Drivers as people who provide services directly to consumers are certainly one of the factors that influence customer behavior in using services. To find out the problems faced by drivers, this research conducts knowledge discovery through topic modeling on GoPartner application reviews using BERTopic, LDA, and NMF, each of these methods has a different approach. Based on the research results and the quality of the topics generated, BERTopic and LDA have better quality in analyzing GoPartner user reviews.